Design of information management systems of incoming and outgoing letters based on web case studies of SDN krajan 02 - Kharisma Ayu Mentari (Universitas Trilogi, 2021)
Administration is an activity of systematically procedures including structured work. If an organization or agency use information technology, the administration will be easier. for the example of an application using information technology about management administration is building an information system to process data from the letters. In this study, researcher designed a mail management information system using HTML, PHP and CSS programming languages hoped that it can speed up the process of managing mail data includes storage using MySQL as database management and speed because it can be accessed online using internet technology anywhere at any time. the results of these studies into the Design and Build Information System for Incoming and Outgoing Mail Management Web-based case studies at SDN Krajan 02